ANALISIS PERBANDINGAN SISTEM DAN PROSEDUR PEMBERIAN KREDIT BANK BRI KONVENSIONAL DAN PEMBIAYAAN MURABAHAH PADA BANK BRI SYARIAH SAMARINDA - Sabri Nurdin; Rafiqoh Rafiqoh; Diana Indriyani Lasabuda (Politeknik Negeri Samarinda, 2019)
This study aims to compare the conventional lending of Bank BRI Conventional and murabahah financing at Bank BRI Syariah Samarinda. The result of the research data are arranged, grouped, then interpreted to obtain a clear flowchart description of the system and proceduresfor conventional lending at Bank BRI Conventional Samarinda and Bank BRI Syariah Samarinda, interviews with bank employees and staff.The result showed that comparative analysis of systems and procedures for granting credit to Bank BRI Conventional and Banl BRI Syariah Samarinda showed that there were two differences in the first Customer Service function in conventional banks and the second if customer funds were liquid. Keywords: System and Procedure, Credit, Bank Conventional And Syariah, Flowchart.